2011
DOI: 10.1007/s10340-011-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance of Maiestas banda (Hemiptera: Cicadellidae), a vector of phytoplasma, and other leafhoppers and planthoppers (Hemiptera: Delphacidae) associated with Napier grass (Pennisetum purpureum) in Kenya

Abstract: Napier grass (Pennisetum purpureum Schumach), the main fodder crop in eastern Africa, has recently been severely affected by Napier stunt disease, which is caused by phytoplasma. We have recently confirmed that a leafhopper, Maiestas banda (Kramer) transmits phytoplasma in Napier grass in Kenya. Several other species of leafhoppers (Cicadellidae) and planthoppers (Delphacidae) are also associated with Napier grass, and some could be potential vector(s) of phytoplasma, but little is known about phenology and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Considering their high population densities, N. fenestratus and P. alienus might have important roles in the plant disease epidemiology cycle in these two agroecosystems. Similarly, high population densities of other leafhopper species, like Maiestas banda (Kramer; Cicadellidae) in Kenya (Koji et al 2012) and Draeculacephala minerva Ball (Cicadellidae) in California (CabreraÐLa Rosa et al 2008), were shown to be involved in the transmission of Napier stunt disease and the bacterium Xylella fastidiosa, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Considering their high population densities, N. fenestratus and P. alienus might have important roles in the plant disease epidemiology cycle in these two agroecosystems. Similarly, high population densities of other leafhopper species, like Maiestas banda (Kramer; Cicadellidae) in Kenya (Koji et al 2012) and Draeculacephala minerva Ball (Cicadellidae) in California (CabreraÐLa Rosa et al 2008), were shown to be involved in the transmission of Napier stunt disease and the bacterium Xylella fastidiosa, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Later, Koji et al. () while using malaise traps showed that these insects were the most abundant species found on Napier grass in western Kenya where NGS disease was first reported (Orodho ), supporting its role in the disease epidemics in the region.…”
Section: Discussionmentioning
confidence: 95%
“…Although the reasons for less disease risk in western Uganda is not known, we presuppose that it is due to limited movement of Napier grass planting materials among farmers since a vast number of them practice extensive farming. Although the vector species responsible for transmission of Napier grass stunt phytoplasma in Uganda are not yet known, Recilia banda (Aauchenorryncha: Cicadellidae) has been reported by Obura et al (2009) to transmit NGSD andKoji et al (2012) found it in high abundance in western Kenya. Therefore, there is a high likelihood that the vector exists in Uganda too, playing a major role in the spread of the disease within and between fields.…”
Section: Discussionmentioning
confidence: 96%
“…The primary means of NGSD spread is through introduction of infested planting materials (cuttings or clump splits) by farmers and/or infected vector carrying the phytoplasma (Orodho, 2006;Koji et al, 2012). Although the vector transmitting NGSD in Uganda is not known, Obura et al (2009) reported Recilia banda Kramer to be the vector of Napier stunt phytoplasma in Kenya.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation